Temporal lobe hypogenesis associated with arachnoid cyst in patients with epilepsy - Kobayashi,Eliane (2003)
OBJECTIVE: To determine the frequency of temporal lobe hypogenesis (TLH) associated with arachnoid cysts (AC) in patients with epilepsy. METHOD: We retrospectively revised 655 consecutive MRI scans from patients followed in our epilepsy clinic. We identified patients with temporal AC and then performed careful visual analysis in a workstation. Patients with evident expansive or destructive lesions were excluded. RESULTS: Only 4 (0.6%) patients had AC in the left temporal lobe, all associated with TLH. In addition, there were also ipsilateral dysgenetic characteristics in the ipsilateral hippocampus including abnormal shape and axis, and hyperintense T2 signal. In one patient this hippocampal abnormality was bilateral. CONCLUSION: AC with TLH was rarely found in our patients with epilepsy and it was always associated with hippocampal dysgenesis. Although volumetric reduction of the temporal lobe can be observed in patients with epilepsy and hippocampal abnormalities, the presence of adjacent AC points to a malformative etiology.